Mixed Convection Flow in a Trapezoidal Cavity with Sinusoidal Heating based on Finite Element Method - Kong, Shii Tsong Jonathan (Enhanced Knowledge in Sciences and Technology, 2023)
This study conducts mixed convection flow in a trapezoidal cavity based on finite element method. The left and right wall is considered adiabatic. The top wall moves with a velocity and the magnetic field strength are present in the cavity. A sinusoidal temperature is utilize on the top of the wall of the cavity. Results shows that when the number of Ri increases, the number of eddies occupied and the temperature distribution on top wall was increased while the temperature on the other wall slightly increases. When there are increases in magnetic field strength, the number of eddies formed also increases. As the Richardson number increase, the average Nusselt number also increase.